2022
DOI: 10.1001/jamaneurol.2022.0003
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Risk Factors and Early Presentations of Parkinson Disease in Primary Care in a Diverse UK Population

Abstract: IMPORTANCEEarly features of Parkinson disease (PD) have been described through population-based studies that overrepresent White, affluent groups and may not be generalizable.OBJECTIVE To investigate the association between risk factors and prediagnostic presentations of PD in an ethnically diverse UK population with high socioeconomic deprivation but universal access to health care. DESIGN, SETTING, AND PARTICIPANTSA nested case-control study was conducted using electronic health care records on 1 016 277 ind… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
50
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 48 publications
(99 reference statements)
5
50
2
1
Order By: Relevance
“…Although an association of hearing loss with Alzheimer disease has long been recognized, this has only rarely been reported for PD. Subjective visual complaints, which are also common in PD, were not a common feature associated with subsequent PD. Unspecified pain, another common sensory feature of PD, was present in a large number of patients before the diagnosis of PD and more common than in controls in all examined time periods as has been previously reported.…”
Section: Discussionmentioning
confidence: 86%
“…Although an association of hearing loss with Alzheimer disease has long been recognized, this has only rarely been reported for PD. Subjective visual complaints, which are also common in PD, were not a common feature associated with subsequent PD. Unspecified pain, another common sensory feature of PD, was present in a large number of patients before the diagnosis of PD and more common than in controls in all examined time periods as has been previously reported.…”
Section: Discussionmentioning
confidence: 86%
“…Hypertension too, while generally showing an inverse association with PD in retrospective case–control studies, has been shown to be associated with future PD in some settings 44 . The relationship between cholesterol and other lipids and PD remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…43 Hypertension too, while generally showing an inverse association with PD in retrospective case-control studies, has been shown to be associated with future PD in some settings. 44 The relationship between cholesterol and other lipids and PD remains unclear. Combining many of these factors into a concept of a metabolic syndrome has been done and suggests that metabolic syndrome and its components may be risk factors for PD.…”
Section: Discussionmentioning
confidence: 99%
“…here is evidence for an association between Parkinson disease (PD) and epilepsy. [1][2][3] Recent observational studies have also established a temporal association between epilepsy and incident PD. 3,4 The mechanism underlying this association remains unclear.…”
mentioning
confidence: 99%